Hyperglycemia-induced oxidative stress in the development of diabetic retinopathy - Thabit Alnahdi, Ahmed; Almujalli, Lama Abdulaziz; Alhawsawi, Sahar Yousef; Gomawi, Raneem Abdurabu; Alhobera, Abdullah Hazza; Alshammari, Khawlah Fares; Alshammari, Mazin Talal; Almuallim, Hisham Muhammedeed; Mubaraki, Gehan Khalid; Shourbaji, Mansour Adel (International Journal Of Community Medicine And Public Health, 2025)
Diabetic retinopathy (DR), the leading cause of preventable blindness, is primarily caused by chronic hyperglycemia-induced oxidative stress. This review examines molecular mechanisms by which hyperglycemia-induced oxidative damage transmits into retinal tissue. We summarize the major pathways: polyol activation, advanced glycation end-products (AGEs), protein kinase C (PKC) dysregulation, and hexosamine pathway. Oxidative stress leads to mitochondrial dysfunction, apoptosis of retinal endothelium and pigment epithelium and activation of cytokines, as well as overexpression of vascular endothelial growth factor (VEGF). These processes together cause vascular leakage, macular edema and pathological angiogenesis. Trials of oxidative stress therapies (e.g. antioxidants, PKC inhibitors e.g., ruboxistaurin, and anti-VEGF agents e.g., ranibizumab, bevacizumab, aflibercept) as well as mitochondria targeted therapies are considered potential therapeutic approaches to improve DR prognosis. Further studies on DR pathophysiology and treatment are recommended to develop effective interventions for this vision threatening condition. Better prevention and management of DR requires early intervention and biomarker-based approaches.